ANALISIS KEKELIRUAN SISWA SEKOLAH DASAR DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Siregar, Nurkhairunnisa (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2023)
This research began because of problems in elementary school students' learning outcomes in mathematics, especially in solving math word problems. One way that can be used to find out the cause of this is to analyze students' mistakes in solving math word problems and the factors that cause student mistakes and solutions to eliminate student mistakes in solving math word problems. The purpose of this study was to describe students' mistakes in solving math word problems. This research is included in the type of qualitative research using descriptive methods. Grade IV students of SD Negeri 200117 Padangsidimpuan were used as subjects in this study. Collecting data in this study using tests, interviews and documentation. Data analysis used is descriptive qualitative analysis. The results of the classical study found that the average percentage of the total number of students who answered correctly was still relatively lower when compared to the average percentage of the total number of students who answered incorrectly. This indicates that there are still many students who are confused or unable to solve math word problems correctly, as evidenced by the percentage of correct answers, which is an average of 46.67% in the sufficient category, while the average total percentage of students who answered incorrectly is higher. that is equal to 53.33%.Keywords: Error Analysis; Story Problems; Mathematics.